'We Were All Strangers Here': Time, Space, and Postcolonial Anxiety in Traversay's Les Amours de Zémédare et Carina, et description de l'île de la Martinique. Issue 2 (9th February 2018) - McCusker, Maeve
Abstract: A sense of dislocation, unsettlement, and exile — what V. S. Naipaul calls the 'enigma of arrival' — was the destiny of all who migrated to the Antilles under the plantation regime, although this enigma was experienced in radically different ways by masters and slaves. While much scholarship exists on how 'black' writers engaged with space and time in the twentieth and twenty-first centuries, earlier Antillean writers have generally not been interrogated in terms of their exploration of the chronotopes of island and plantation. For these writers, fiction was a medium through which to explore and accentuate the exotic: nineteenth-century novels routinely present idealized, mysterious, magical, or forbidding landscapes. Fiction also provided a powerful vehicle for domesticating the alien, through a pronounced recourse to (apparently) objective detail and quantifiable data. This article examines the first known, and almost entirely neglected, Martiniquan novel, Traversay's Les Amours de Zémédare et Carina, a novel that exemplifies this tension between the urge to make strange and the urge to chart, define, and explain. In its treatment of time — in particular its use of prolepsis — and in the presentation of space — gardens, trees, geological formations — the novel exemplifies the ambivalence and anxiety so commonly identified with more recent postcolonial writing.